Long-term changes (1800–2019) in marine vegetational habitats: Insights from a historic industrialised coastal area. (October 2020) - Lucia, Porzio; Grech, Daniele; Buia, Maria Cristina
Abstract: Macrophytes play an important structural and functional role in marine ecosystems but are experiencing a considerable decline in many areas of the Mediterranean Sea. Despite the long tradition of studies on vegetated marine habitats in the Gulf of Naples (Italy), a gap of knowledge on their long-term dynamics has recently been highlighted, mainly in the most anthropised areas. This work aimed to provide insights from the historic industrialised coastal area of the Site of National Interest (SIN) Bagnoli-Coroglio (Gulf of Pozzuoli, Italy), after decades of chemical contaminations and coastal transformation, to build a baseline for the next remediation and restoration programs. Historical occurrence of macroalgae and seagrasses before, during and after the industrial period was assessed; in particular, we focused the attention mainly on habitat-forming species, due to the vital function played in the trophic net. We observed no differences in the macroalgal diversity between the SIN district and the other parts of the Gulf of Pozzuoli, except for the Gulf of Pozzuoli during the industrial period, where the biodiversity showed a decreasing trend. However, a substantial regression of the largest macrophytes (Fucales) on rocky coasts and of marine monocots on sandy bottoms, all over the area, has been recorded. A loss of about 70% has concerned seagrass cover, mainly Posidonia oceanica, in the contaminated area of the SIN: at present, this engineering species is missing on the bottom, facing the industrialised area. The human-made coastline transformation, the lack of natural substrates and the spatial remoteness among donor populations seem to be the leading causes of the significant decrease, over time, of marine forests in this study area. These factors should be taken into account to establish conservation priorities and for plant restoration. Highlights: Marine vegetational habitats are the most sensitive descriptors to assess environmental changes. Long-term data on macrophytic diversity and distribution were provided for the Italian SIN Bagnoli-Coroglio. A complete list of macroalgae since the nineteenth century is reported for the whole Gulf of Pozzuoli. A severe loss of Fucales and seagrass meadows has been detected. Human-made coastline seems the leading cause of vegetational habitats regression.